2014
DOI: 10.1103/physrevd.89.064014
|View full text |Cite
|
Sign up to set email alerts
|

Scalar Green function of the Kerr spacetime

Abstract: In this paper we study the scalar Green function in the Kerr spacetime using Wentzel-Kramers-Brillouin (WKB) methods. The Green function can be expressed by Fourier-transforming to its frequency-domain counterpart, and with the help of complex analysis it can be divided into parts: 1) the "direct part," which propagates on the light cone and dominates at very early times; 2) the "quasinormal-mode part," which represents the waves traveling around the photon sphere and is important at early and intermediate tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 45 publications
(164 reference statements)
7
53
0
Order By: Relevance
“…This view has already been confirmed by many investigations [44,45,46,47,48,49,50,51,52,53]. One conclusion from these studies was that joint measurements of the geometry and dynamical observations found that the interaction rate, Q, was zero at about 1σ [30,31,32,33]. Unfortunately, this conclusion has been drawn using the intervals w x ≤ −1 and w x ≥ −1 separately.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…This view has already been confirmed by many investigations [44,45,46,47,48,49,50,51,52,53]. One conclusion from these studies was that joint measurements of the geometry and dynamical observations found that the interaction rate, Q, was zero at about 1σ [30,31,32,33]. Unfortunately, this conclusion has been drawn using the intervals w x ≤ −1 and w x ≥ −1 separately.…”
Section: Introductionmentioning
confidence: 79%
“…Following this, interaction term Q = 3Hξρ x needs to be tested against the observations with two intervals for dark-energy equation of state w x ≤ −1 and w x ≥ −1 [29,30,31,32,33]. We note that w x = −1 is the limiting case, see [29] for details.…”
Section: Background and Perturbation Evolution In Coupled Dark-energymentioning
confidence: 99%
See 2 more Smart Citations
“…The second correction term has also appeared in the entropic cosmology introduced in [42]. While positive and negative values have been suggested for α and β by some authors [43]- [47], it has also been argued that the best guess to the logarithmic term might simply be zero [48]. A stable flat entropy-corrected FRW universe with a decelerationacceleration transition has been constructed in [49] for zero values of both pre-factors.…”
Section: Introductionmentioning
confidence: 99%